Une île déserte déjà exploitée ? - Taichi Nakae (Carnets)
Readers would be surprised by the fact that the desert island where Robinson Crusoe is stranded is inhabited almost exclusively by European fauna: cats, rabbits and goats. Although this novel has been the subject of postcolonial criticism and ecocriticism since the late 20th century, it seems that not enough attention has been paid to this apparent paradox: why do European animals already inhabit the land where Robinson is supposedly the first European to set foot? In this article, we will first attempt to interpret Robinson Crusoe as a narrative of the erasure of debts and borrowing, by comparing it to the travel account written by Woodes Rogers, which is supposed to have inspired Daniel Defoe to write his first novel. Then, referring to Alfred Crosby's concept of “ecological imperialism", we will propose a new perspective in the analysis of the robinsonade by inserting it into the history of colonization.